Digital photographic technique for the production of an artificial eye. (3rd April 2021) - Zoltie, Timothy; Bartlett, Paul; Archer, Tom; Walshaw, Emma; Gout, Taras
Abstract: The use of hand painting an iris button using oil paint remains the conventional method of artificial eye manufacturing. The authors found that replacing this technique with a digital photograph taken of a patient's unaffected eye offers several advantages over the conventional method but the process from capture to print must be standardised and colour accurate. The authors of this paper suggest a tried and tested formulated photographic process of capture and printing prior to polymerisation. It discusses issues that can arise and how these can be overcome in order to achieve a high-quality print that can be used to produce a 'life like' ocular prosthesis.